بمالانج (MAN I) استخدام القاموس الإلكترونية المترجم واستخدامها في ترجمة نصوص العربية بالمدرسة الثانوية الحكومية - maghfur, Ahmad ‘Ali; Suryanto, Ardiansyah Bagus (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2020)
This article was conducted to solve the problems faced by students regarding the difficulty of understanding Arabic text in class X textbooks. And applications are offered to solve these problems with the Mutarjim dictionary application which can help and make it easier for them to access Arabic vocabulary quickly and easily. The method used is descriptive qualitative, data obtained by interviews. Then data was collected which eventually found various problems. Departing from this problem, the data is analyzed so that it finds a solution for solve it. From the research results found a solution, namely by using the Mutarjim dictionary as a tool in translating Arabic text. The steps are (1) enter text; (2) choose the base word in the vocabulary (3) read the whole equivalent in the target text; (4) looking for the right equivalent in accordance with the culture contained in the source language and target language